Mortality and associated risk factors in patients with severe methanol or ethylene glycol poisoning treated with dialysis: a retrospective cohort study - Kuusela Emma; Järvisalo Mikko J; Hellman Tapio; Uusalo Panu (SAGE PUBLICATIONS LTD, 2022)
Objective To compare the initial clinical course and data on 90-day mortality in adults with methanol (MET) or ethylene glycol (EG) poisoning treated with dialysis. Methods Data on patient demographics and clinical parameters at intensive care unit (ICU) admission and for the first 24 hours after dialysis initiation were collected, and 90-day outcome data were collected for patients with MET (n = 15) or EG (n = 13) poisoning treated with dialysis in this retrospective cohort study. Results In univariate analysis, patients with EG poisoning were older and they had lower hourly urine output during the first 24 hours after the initiation of dialysis. Six (46%) patients with MET poisoning and three (20%) patients with EG poisoning died within 90 days of ICU admission. A larger anion gap and lower pH, bicarbonate levels, base excess, and Glasgow Coma Scale scores on admission, as well as the need for mechanical ventilation, were associated with 90-day mortality. Conclusions Metabolic acidosis, a large anion gap, and an altered mental status on admission appear to be associated with mortality in MET or EG poisoning, and EG poisoning may be linked to lower urine output.